El folklore como agente político: la Nueva Canción Chilena y la diplomacia musical (1970-1973) - Javier Rodriguez Aedo (Nuevo mundo - Mundos Nuevos, 2017)
The Chilean New song movement represents an important episode in the debate around folklore and political song during the period of Popular Unity. Despite the existence of numerous studies, mostly concerned with understanding the origins and implications of the movement in Chile, few works have tried to surpass the national perspective of analysis, in order to understand the musical and political interactions in the international context. Through the study of three moments and three different musical spaces, this article seeks to understand the role of Chilean musicians in the diffusion of ideas about folklore and politics under the context of the Cold War, focusing on the elements that confirm this original experience of the musical diplomacy during the years of the revolutionary process in Chile.